Experimental estimation of the bisulfite isomer quotient as a function of temperature: Implications for sulfur isotope fractionations in aqueous sulfite solutions. (1st January 2018) - Eldridge, Daniel L.; Mysen, Bjorn O.; Cody, George D.
Abstract: Bisulfite (HSO3 − ) and sulfite (SO3 2− ) compounds play key roles in numerous geochemical and biochemical processes extending from the atmosphere to the subseafloor biosphere. Despite decades of spectroscopic investigations, the molecular composition of HSO3 − in solution remains uncertain and, thus, the role of bisulfite in (bio)chemical and isotope fractionation processes is unclear. We report new experimental estimates for the bisulfite isomer quotient ( Q i  = [(HO)SO2 − ]/[(HS)O3 − ]; [] = concentration) as a function of temperature from the interpretation of Raman spectra collected from aqueous NaHSO3 solutions contained in fused silica capsules. In pure NaHSO3 solutions (1Na + :1HSO3 −, stoichiometric) over [NaHSO3 ] = 0.2–0.4 m (moles/kg H2 O), the following relationship is obtained: ln ( Q i ) = 878.59 ( ± 32.98 ) T - 1.9642 ( ± 0.1081 ), where T = 278–358 K (5–85 °C) (based on 50 determinations; additional significant figures are provided to avoid rounding errors). This relationship suggests that the minor isomer, (HS)O3 −, may comprise 23–38% (±3%) of the mole fraction of HSO3 − over 5–85 °C, respectively, which is higher in relative abundance than has generally been understood previously. We additionally provide estimates for Q i in NaHSO3 solutions containing a total ionic strength of µ  = 1.0 m (0.2 m NaHSO3  + 0.8 m NaCl) and different pH (3.3–4.5), but do not appear to resolve any significant differences in Q i as a function of these additional variables. These new values of Q i are employed to re-assess the bulk sulfur isotope fractionations among bisulfite and other S(IV) compounds as a function of temperature, which appear to be highly dependent on the amount of (HS)O3 − present. Our new constraints on the bisulfite isomer quotient may allow for a detailed assessment of the molecular composition and isotope mass balance of S(IV) solutions containing HSO3 −, and may be useful in the further investigation of the mechanisms and isotope fractionations associated with a number of processes that involve bisulfite compounds. These may include the intracellular enzymatic transformations of sulfite and bisulfite compounds that occur as part of dissimilatory sulfate reduction, which is a major and geologically important form of anaerobic respiration.